2013
DOI: 10.2172/1172118
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Energy-efficiency and Carbon Dioxide Emissions-reduction Technologies for the Iron and Steel Industry

Abstract: Iron and steel manufacturing is among the most energy-intensive industries and accounts for the largest share, approximately 27 percent, of global carbon dioxide (CO 2 ) emissions from the manufacturing sector. The ongoing increase in world steel demand means that this industry's energy use and CO 2 emissions continue to grow, so there is significant incentive to develop, commercialize and adopt emerging energy-efficiency and CO 2 emissions-reduction technologies for steel production. Although studies from aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 45 publications
(61 reference statements)
0
24
0
3
Order By: Relevance
“…Existing technologies are included in the model from the start period onward. Definitions of existing and emerging energy-efficient technologies used in this study can be found in U.S. EPA [64], Hasanbeigi et al [65], and Worrell et al [66].…”
Section: Selection Of Energy-efficient Technologiesmentioning
confidence: 99%
“…Existing technologies are included in the model from the start period onward. Definitions of existing and emerging energy-efficient technologies used in this study can be found in U.S. EPA [64], Hasanbeigi et al [65], and Worrell et al [66].…”
Section: Selection Of Energy-efficient Technologiesmentioning
confidence: 99%
“…There are two different processes of agglomeration which are used in industry: sintering and pelletizing. Sintering plants are usually located near the blast furnace site, while pelletizing plants are situated near the mines [31]. From the range of data collected, the average energy required for this process is 1.59 ± 0.36 GJ/t of iron agglomerate (Table 6).…”
Section: Pig Iron Productionmentioning
confidence: 99%
“…In some countries like Brazil, charcoal is commonly used in the production of pig iron instead of coke. 4.45 [22] 3.59 [36] 5.80 [38] 2.40 [31] 6.00…”
Section: Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Em face à pressão das mudanças climáticas no setor, a redução do consumo de energia, bem como das emissões de Gases de Efeito Estufa (GEE) estão na agenda. A produção de ferro e aço está entre as mais intensivas em uso de energia e corresponde à maior parcela de emissão de CO2 do setor manufatureiro, aproximadamente 27% [6]. Uma gama de tecnologias de baixo consumo de energia e de emissão aplicáveis à indústria siderúrgica já estão em estado de comercialização.…”
Section: Introductionunclassified